Efektivitas Aromaterapi terhadap Kualitas Tidur dan Kecemasan - Vania Pangestika Purwaningrum; Fitria Handayani Handayani; Dwi Pudjonarko (Journal of Telenursing (JOTING), 2023)
This study aims to determine the effectiveness of aromatherapy on sleep quality and anxiety in elderly adult population patients. The method used is a systematic review related to the management of sleep disorders and anxiety with aromatherapy. The results showed that aromatherapy given by inhalation and massage methods with lavender, rosa damascene, chamomile and neroli essential oils for at least three nights and a maximum of thirty days was considered to have an effect on sleep quality and anxiety. Conclusion, aromatherapy is effective in improving sleep quality and reducing anxiety. Keywords: Anxiety, Aromatherapy, Sleep Quality